Wpływ działalności Zakładów Chemicznych "Złotniki" we Wrocławiu na środowisko glebowe terenów przyległych w świetle całkowitej zawartości metali ciężkich = Impact activity of the Chemical Works "Złotniki" in Wrocław on soil environmental of adject areas in the light of total content of heavy metals - Musztyfaga, Elżbieta; Cuske, Mateusz; Pora, Ewa; Szopka, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses issues related to the impact of the Chemical Works "Złotniki" SA in Wrocław on soil conditions of areas in the immediate vicinity. Analyses show that the activity of the object significantly affect of the level of enrichment metallic elements in adjacent areas. It was overenrichment of copper and zinc I analyzed soils.
Keywords: gleby zanieczyszczone; metale ciężkie; Zakłady Chemiczne Złotniki; contaminated soils; heavy metals; Chemical Works Złotniki